Spring Migration and Subsistence Hunting of King and Common Eiders at Holman, Northwest Territories, 1996-98 - Byers, Tim; Dickson, D. Lynne (ARCTIC, 2001)
A subsistence hunt for eiders by Innuvialuit of Holman, Northwest Territories, was observed over three spring harvest seasons from 1966 to 1998 to determine rates of crippling loss and to assess the sustainability of the harvest. King eiders (Somateria spectabilis) are the dominant waterfowl species harvested. The number of king eiders estimated to migrate past Holman in spring varied from 40 696 ± 4461 (95% confidence interval) in 1996 to 70 018 ± 14 356 in 1998, averaging 53 000 per year. Common eiders (Somateria mollissima v-nigra) were much less abundant, varying from 2728 ± 631 to 6017 ± 770 birds, averaging 4400 annually. Peak numbers of king eiders moved through the study area in 1-8 days during the second to third week of June in all years, and common eiders peaked in 1-8 days during the first to second week of June. Strong winds may have hindered migration for a few days. Crippling loss rates during the hunt were low (3-9%) in the first two years of the study, but increased to 13-20% in the early open-water spring of 1998, when hunters were forced to shoot over open water rather than shorefast ice. On the basis of these estimates and harvest data from the Inuvialuit Harvest Study, we determined that Holman hunters removed 3.7-6.9% of the king eider subpopulation and less than 1% of the common eiders over the three-year study period. The present level of harvest of eiders available to Holman hunters is likely sustainable. However, more information on natural mortality and recruitment rates, particularly for king eiders, is needed to confirm this. La chasse de subsistance à l'eider menée par les Inuvialuit de Holman (Territoires du Nord-Ouest) a fait l'objet d'un étude sur les trois saisons de récoltes printanières allant de 1996 à 1998, afin de déterminer les taux de pertes dues aux blessures et d'évaluer la viabilité de la récolte. L'eider à tête grise (Somateria spectabilis) représente la plus importante espèce de sauvagine récoltée. L'estimation du nombre d'eiders à tête grise passant près d'Holman ...